On the anticoagulant and antiaggregatory properties of a glucosamine sulfate molecule - I. Yu. Torshin; A. M. Lila; O. A. Gromova; A. V. Naumov; A. N. Gromov (Современная ревматология, 2019)
Glucosamine is part of the human metabolome required for the biosynthesis of polymer glycosaminoglycans in connective tissue. In addition, the glucosamine molecule itself has anti-inflammatory and regenerative properties. This paper presents the results of a systematic analysis of fundamental and clinical studies, which indicate the anticoagulant and antiaggregatory effects of a highly purified pharmaceutical substance of microcrystalline glucosamine sulfate (mGS). The main molecular mechanisms of its antithrombotic effects are most probably the mGS molecular mimicry of heparan sulfate activity, the activation of CD44 receptor, and the inactivation of the NF-KB signaling pathways in platelets. A quantitative chemoreactome study has shown that the antithrombotic effects of mGS in the human reactome are due to the inhibition of: ’) proper platelet aggregation; 2) platelet adhesion and activation receptors; 3) endogenous synthesis of thromboxanes; 4) coagulation by reducing the activity of coagulation factors.